Enhancing the effectiveness of state management of private archives - Dang Thi Thu Phuong (Journal of State Management, 2025)
State management of private archives is an essential requirement in modern society. Effectively carrying out this task contributes to protecting national security, safeguarding individuals' and organizations' legitimate rights and interests, and supporting state management and socio-economic development. This article analyzes the need to improve the effectiveness of state management of private archives in the current context and proposes a number of solutions.